Wallacean and Melanesian Islands Promote Higher Rates of Diversification within the Global Passerine Radiation Corvides. (15th June 2022) - McCullough, Jenna M; Oliveros, Carl H; Benz, Brett W; Zenil-Ferguson, Rosana; Cracraft, Joel; Moyle, Robert G; Andersen, Michael J
Abstract: The complex island archipelagoes of Wallacea and Melanesia have provided empirical data behind integral theories in evolutionary biology, including allopatric speciation and island biogeography. Yet, questions regarding the relative impact of the layered biogeographic barriers, such as deep-water trenches and isolated island systems, on faunal diversification remain underexplored. One such barrier is Wallace's Line, a significant biogeographic boundary that largely separates Australian and Asian biodiversity. To assess the relative roles of biogeographic barriers—specifically isolated island systems and Wallace's Line—we investigated the tempo and mode of diversification in a diverse avian radiation, Corvides (Crows and Jays, Birds-of-paradise, Vangas, and allies). We combined a genus-level data set of thousands of ultraconserved elements (UCEs) and a species-level, 12-gene Sanger sequence matrix to produce a well-resolved supermatrix tree that we leveraged to explore the group's historical biogeography and the effects of the biogeographic barriers on their macroevolutionary dynamics. The tree is well resolved and differs substantially from what has been used extensively for past comparative analyses within this group. We confirmed that Corvides, and its major constituent clades, arose in Australia and that a burst of dispersals west across Wallace's Line occurred after the uplift of Wallacea during the mid-Miocene. We found that dispersal across this biogeographic barrier was generally rare, though westward dispersals were two times more frequent than eastward dispersals. Wallacea's central position between Sundaland and Sahul no doubt acted as a bridge for island-hopping dispersal out of Australia, across Wallace's Line, to colonize the rest of Earth. In addition, we found that the complex island archipelagoes east of Wallace's Line harbor the highest rates of net diversification and are a substantial source of colonists to continental systems on both sides of this biogeographic barrier. Our results support emerging evidence that island systems, particularly the geologically complex archipelagoes of the Indo-pacific, are drivers of species diversification. [Historical biogeography; island biogeography; Melanesia; molecular phylogenetics; state-dependent diversification and extinction.]